2014
DOI: 10.1002/acn3.67
|View full text |Cite
|
Sign up to set email alerts
|

Laquinimod reduces neuroaxonal injury through inhibiting microglial activation

Abstract: ObjectiveLaquinimod is an emerging oral medication for multiple sclerosis (MS) that reduces brain atrophy and progression of disability in two Phase III clinical trials. The mechanism of these effects is unclear. Persistent activation of microglia occurs in MS and contributes to injury. Thus, we investigated whether laquinimod alters properties of microglia in culture and in experimental autoimmune encephalomyelitis (EAE), and whether this reduces neurodegeneration.MethodsMicroglia were cultured from human bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 41 publications
4
79
0
Order By: Relevance
“…QSM measurement of chronic inflammation in MS lesions that appear stable on conventional MRI but have a high burden of lesional microglial activation are of significant therapeutic and diagnostic importance. Several compounds that are either FDA approved (Tecfidera) or under development (Laquinimod (170) and Siponimod (171)) have been shown to impact microglial activation (172,173). QSM can be utilized to monitor these therapies for their ability to mitigate iron accumulation in microglia.…”
Section: Clinical Applications Enabled By Qsm Biometal Imagingmentioning
confidence: 99%
“…QSM measurement of chronic inflammation in MS lesions that appear stable on conventional MRI but have a high burden of lesional microglial activation are of significant therapeutic and diagnostic importance. Several compounds that are either FDA approved (Tecfidera) or under development (Laquinimod (170) and Siponimod (171)) have been shown to impact microglial activation (172,173). QSM can be utilized to monitor these therapies for their ability to mitigate iron accumulation in microglia.…”
Section: Clinical Applications Enabled By Qsm Biometal Imagingmentioning
confidence: 99%
“…Mice treated with laquinimod before onset of clinical signs had marked reduction in microglia/macrophage density and axonal injury/loss. In addition, treatment with laquinimod halted disease progression and production of inducible nitric oxide, thus attenuating the neurodegeneration associated with EAE (Mishra et al 2014).…”
Section: Laquinimodmentioning
confidence: 99%
“…In vivo studies have shown that laquinimod reduces leukocyte infiltration to the CNS, induces a shift from cytotoxic Th1 to Th2/ 3, and dampens the Th17 responses in the EAE model (Yang et al 2004;Wegner et al 2010). In the context of microglia, laquinimod is a novel inhibitor of microglial activation that decreases microglial-induced neuronal cell death in vitro and axonal degeneration/loss in vivo (Mishra et al 2014). In EAE, axonal injury is often correlated with the accumulation of microglia/macrophages in the spinal cord.…”
Section: Laquinimodmentioning
confidence: 99%
“…The influence of laquinimod on the immune system was studied in experimental autoimmune encephalomyelitis (EAE) (4)(5)(6)(7)(8)(9)(10)(11)(12), an autoimmune disease mediated by proinflammatory myelinreactive lymphocytes that cause CNS inflammation leading to demyelination and axonal loss. Laquinimod has also been effective in the treatment of other models of autoimmune diseases, specifically experimental autoimmune neuritis (13,14), lupus nephritis (15), and colitis (16).…”
mentioning
confidence: 99%